Anarchitecture. - Benedetti, Lorenzo; Dorn, Anja; Harada, Machiko; Tufnell, Rob; van de Ven, Suzanne (Amsterdam : De Appel Foundation, 1999)
Bain, Mark ; Bjarnason, Thoroddur ; Boyce, Martin ; Braun, Matti ; Demand, Thomas ; Frankland, John ; Galegati, Stefanie ; Hunneman, Hendrik Jan ; Jacobi, Frans ; Petersen, Lars Bent ; Schneider, Gregor ; Zuff, Italo
biog., ind. tent., gr. tent. [6 p.]
Anarchitecture, De Appel Foundation, Amsterdam, April 09 - June 06. 1999
Engels
boek